Larval aggression is independent of food limitation in nurseries of a poison frog - Dugas, Matthew B. (2016)
Aggression between nurserymates is common in animals and often hypothesized to result from proximate resource limita- tion. In numerous terrestrial frogs, larvae develop in phytotelmata, tiny water bodies where resources are scarce and competition, aggression, and cannibalism are all common between individuals sharing these nurseries. In some species, mothers provision phytotelm-bound young with trophic eggs, a strategy that compensates for low nutrient availability and could allow mothers to reduce costly aggression and cannibal- ism among nurserymates. We tested this hypothesis using strawberry poison frog (Oophaga pumilio) tadpoles, staging secondary depositions in arenas occupied by residents that had either been food deprived or fed ad libitum. Resident tadpoles were nearly all aggressive and most killed intruders, but aggression was unrelated to resident food deprivation. Unlike most related frogs studied, O. pumilio residents did not cannibalize their victims. This result supports the hypothesis that proximate food limitation and aggression can be independent.